2016
DOI: 10.1002/cphc.201501118
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configuration from Different Multifragmentation Pathways in Light‐Induced Coulomb Explosion Imaging

Abstract: The absolute configuration of individual small molecules in the gas phase can be determined directly by light-induced Coulomb explosion imaging (CEI). Herein, this approach is demonstrated for ionization with a single X-ray photon from a synchrotron light source, leading to enhanced efficiency and faster fragmentation as compared to previous experiments with a femtosecond laser. In addition, it is shown that even incomplete fragmentation pathways of individual molecules from a racemic CHBrClF sample can give a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…Confirming our previous work [23], the electron energy spectra for the fragmentation into four cations do not show any structures. This could be due to the physical processes leading to this fragmentation or due to experimental limi- tations that do not allow to detect four electrons in coincidence correctly.…”
Section: Site-selective Excitationsupporting
confidence: 90%
See 1 more Smart Citation
“…Confirming our previous work [23], the electron energy spectra for the fragmentation into four cations do not show any structures. This could be due to the physical processes leading to this fragmentation or due to experimental limi- tations that do not allow to detect four electrons in coincidence correctly.…”
Section: Site-selective Excitationsupporting
confidence: 90%
“…Information on the absolute configuration can also be obtained from fragmentation pathways involving neutral dissociation products, as long as suitable ionic fragments are detected [23]. For these 'incomplete' break-ups, the assignment of masses becomes ambiguous: First, the isotopes of chlorine and bromine can no The same condition for the ions' momenta was set for investigating the break-ups {H + , Cl + , Br + , CF + 3 } and {H + , Cl + , Br + , CF + 2 }, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…molecules with the same chemical formula but different geometric structures, from the fragmentation patterns. For example, it was demonstrated that it is possible to separate two enantiomers in a racemic mixture of small chiral molecules by measuring five-fold ion coincidences after strong-field ionization [6,13] or beam-foil induced Coulomb explosion [30], while three-fold ion coincidences after inner-shell photoionization were used to identify the cis and trans geometric isomers of dibromoethene [31].…”
Section: Introductionmentioning
confidence: 99%
“…All of these experiments have employed the Coulomb explosion coincidence momentum imaging technique16171819, in which all charged fragments that are created when the multiply charged parent ion breaks up (“ explodes ”) are measured in coincidence and their momentum vectors are used to extract information about the dynamical change in the geometry of the parent molecule. Recently, this technique was also used to separate two enantiomers in a racemic mixture of the chiral molecules CHIClF and CHBrClF by measuring five-fold coincidences after strong-field laser ionization2021, and the related beam-foil Coulomb explosion method was used to study the absolute configuration of trans-2,3-dideuterooxirane (C 2 H 2 D 2 O)22.…”
mentioning
confidence: 99%